Closer adult child–parent relations the stronger the vaccine hesitancy: A cross-sectional study of adult Children’s attitudes toward pneumococcal vaccination of elderly parents and its determinants in Guangzhou, China - Qiqi Wu; Haiyuan Zhu; Runquan Zhang; Cuizhi Li; Qin Xiao; Yuqing Jin; Xiaofeng Liang; Xiongfei Chen; Xiaomei Dong (Human Vaccines & Immunotherapeutics)
Pneumococcal disease (PD) has a serious effect on older people aged 60 years and above. However, pneumococcal vaccination rates for older people in China remain low. This study aimed to explore adult children’s perspectives on the vaccination of their parents and to examine the determinants of vaccine hesitancy. In October 2022, a cross-sectional survey was conducted in Guangzhou, China. The questionnaire assesses data on the sociodemographic characteristics of adult children and their parents, health beliefs about vaccination, and variables measuring adult child–parent relationships. Adult child–parent relationships types were identified by Latent Class Analysis (LCA). Binary logistic regression was employed to examine the factors associated with vaccine hesitancy. A total of 1,597 respondents were enrolled in the study, and 59.8% of the adult children expressed hesitancy about vaccinating their elderly parents. The LCA model identified three distinct types of adult child–parent relations: detached, intimate but distant, and tight-knit. Binary logistic regression analyses revealed that respondents with intimate but distant (OR = 3.04) and tight-knit (OR = 3.01) adult child – parent relationships, high literacy (OR = 2.63), and high perceived barriers of vaccine (OR = 1.18) were more likely to be hesitant. Conversely, those with high income (OR = 0.35) and parents with difficulties in activities of daily living (OR = 0.44) were less likely to exhibit vaccine hesitancy. Close adult child–parent relations were positively associated with vaccine hesitancy. Health education related to the vaccination of older persons should be extended to adult children.